(3Wja GdNjGd aj eYQaI NjGd GdXds - (3eMeO Hf OGfjGd Hf jhSa GdNRGYj GdehUdj, GHf OGfjGd , TeS GdOjf GdcMGd,J (B710 (3g` s
(3ChdgG (B:s
(3cJHJ Edi CjgG GdCSJGP GdHOjY hjbhd NjGdfG dCgd GdQJH hGdaVd hGdHPd hCgd GdCOH Mhi afhf GdgRd hGdMPbi CMSf Tcd hCJi HGdYLH s
(3BNQgG (B:s
(3ajfJHg Gdbhe ef GdZadI hGdfhe hjQhf Pdc GdMGd JeJ GdKGdKI ef cJGH Wja GdNjGd HJeGegG hGdceGd hGdMeO ddg hGgH GdYbd heajV GdLhO s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B120 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B295s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdeYGQa GdYGeIs